Batch Deterministic and Stochastic Petri nets Modeling for Reliability Quantification for Safety Critical Systems of Nuclear Power Plants - Kumar Jyotish N.; Kumar Singh L.; Kumar C.; Singh P. (My University, 2025)
Safety-critical systems (SCS) are essential in maintaining and controlling the nuclear power plant (NPP) facilities, providing feedback on the plant's conditions, and safeguarding it from adverse consequences i.e., SCS plays a vital role in NPP. Thus, failure of such systems can lead to massive financial losses, human resource damage, and environmental degradation. It is, therefore, important that these systems should have a high level of reliability and accuracy. This research introduces a novel method for designing and assessing the reliability of SCS by employing batch deterministic & stochastic Petri nets (BDSPNs) and Markov chain. Our method of reliability evaluation achieved 99.9905% accuracy, proving its effectiveness. This paper illustrates the proposed approach to NPP's Shutdown System (SDS). © 2023 Elsevier B.V.